Car Storage Warehouse Information System Using the LIFO Method - andy wildan romadhoni; Salamun Rohman Nudin (Universitas Negeri Surabaya, 2026)
Warehouse management in car rental businesses requires an efficient system to manage vehicle storage and retrieval processes. However, many existing systems still rely on manual recording or focus primarily on transaction management without integrating inventory prioritization methods, resulting in inefficient vehicle rotation and increased operational errors. This study aims to develop a web-based car storage warehouse information system that implements the Last In First Out (LIFO) method to improve storage efficiency and decision-making processes. The system is developed using the Research and Development (R&D) approach and the Waterfall model, with implementation based on PHP and MySQL. The LIFO mechanism is applied by prioritizing vehicles based on the most recent entry timestamp. The evaluation results show that the system reduces vehicle selection time from 3-5 minutes in manual processes to 5-10 seconds, representing an efficiency improvement of approximately 95%, while achieving 100% consistency in vehicle selection. This study contributes by integrating LIFO-based inventory control into a practical web-based warehouse system, providing a more structured, efficient, and accurate solution for vehicle storage management.